Un díptico ovidiano: Numa, Augusto y el poeta en los Fastos a la luz de las Metamorfosis - Martínez Astorino, Pablo (2021)
The article proposes to analyze the Fasti's Numa in relation to that of the Metamorphoses, considering: (1) the Ovidian representation of the monarchy; (2) the link between Numa and Augustus as a peacemaker; (3) the link between Numa and the poet. The conclusion to be reached is that, although Ovid, through Numa, represents in the Fasti a sort of contrafactual Augustus post Actium, in the light of the Metamorphoses, where the Numa's association with Augustus through the motif of pax leads to the poet, the image of the contrafactual Augustus cannot be understood as the end of the representation, but it is resolved in the image of an Augustus-Numa that, added to that of the Metamorphoses, constitutes a diptych, a double and complementary contemporary representation, which also in Fasti, though in a different way, leads to the poet, showing the primacy of poetry over politics in Ovidian writing.